Função de recuperação do nervo auditivo após doze meses de uso do implante coclear - YAMAGUCHI, Cíntia Tizue (Universidade Federal do Pará, 2022)
Introduction: Cochlear implant is the standard treatment for severe and profound bilateral sensorineural hearing loss. To optimize the adaptation of this device, especially in patients who do not have the ability to refer to the parameters necessary for programming, such as children and people with associated disabilities, objective tests based on the action potential of auditory nerve fibers have been studied as possible predictors. of these parameters to be used in cochlear implant programming. The auditory nerve recovery function is a test that measures the time the auditory nerve needs to recover from a stimulus (leave the absolute refractory period) to receive new stimulation and possibly be more responsive to the auditory sensation offered by the cochlear implant. Objective: Through a specific software for cochlear implants, with the objective of measuring the time constant (τ) in the intraoperative period and in the postoperative period after 12 months of cochlear implant use in children. Method: We recruited children with cochlear implant and intraoperative neural response, evaluated the recovery function using commercially available cochlear implant software. Data were collected intraoperatively and repeated twice 12 months after surgery. Results: We found that the recovery time of the auditory nerve increases after 12 months of cochlear implant use. Our results also show that the profile of temporal responses is significantly higher in the postoperative measurement than in the intraoperative one. The test-retest reproducibility of the composite evoked action potential recordings proved to be reliable and stable. Conclusion: There was a change in 12 months of cochlear implant use, in relation to the same measure at the intraoperative moment in the subjects of this study. The intraoperative τ measurement was faster, however, in the postoperative period the mean showed higher τ values. However, the current level was different intraoperatively and 12 months after use, needing to be further explored. There was no statistical difference regarding the test-retest in the postoperative period, showing reliability and reproducibility of the measurement. Possibly it would be the beginning of the study of a responsiveness profile in relation to the recovery time of the auditory nerve.